Diversity-Oriented Stereocontrolled Synthesis of Some Piperidine- and Azepane-Based Fluorine-Containing β-Amino Acid Derivatives - Nonn, Melinda; Kara, Dominika; Ouchakour, Lamiaa; Forró, Enikő; Haukka, Matti; Kiss, Loránd (Synthesis, 2020)
Structural diversity-oriented synthesis of some azaheterocyclic β-amino acid derivatives has been accomplished by selective functionalization of readily available cyclodienes. The stereocontrolled synthetic concept was based on the oxidative ring cleavage of unsaturated cyclic β-amino acids derived from cycloalkadiene, followed by ring closing with double reductive amination, which furnished some conformationally restricted β-amino acid derivatives with a piperidine or azepane core.
Keywords: azaheterocyles; structural diversity; amino acids; stereocontrol; selectivity